Regional Competences in public security. A vector of inequality and its aggravation in the Autonomous Community of Aragón - Muñoz Tabernero, Óscar Antonio (Revista de derecho aragonés, 2024)
The constitutional and legally established exceptions to the Autonomous Regions competence over public security lead to inequality in the rights of citizens residing in the different autonomous territories. In the Autonomous Region of Aragon, this inequality is aggravated by an abandoned and, in any case, ineffective and inefficient exercise of the competence which, with a direct impact on public safety, the Autonomous Region has, such as coordination and other powers with respect to the Local Polices of Aragon.